BASED ON THE WORKS OF EASTERN THINKERS DEVELOPMENT OF MORAL QUALITIES IN STUDENTS - Irgashova Maripat Abdinazarovna (Journals Park Publishing, 2024)
This article presents the views of thinkers on the development of moral qualities in students. The categories of morality are listed.
Keywords: student, pedagogical skill, education, training, personality, system, patterns, form, goal.